(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Navia ZI, Audira D, Afifah N, Turnip K, Nuarini, Suwardi AB. 2020. Ethnobotanical investigation of spice and condiment plants used by the Taming tribe in Aceh, Indonesia. Biodiversitas 21: 4467-4473. Communities are inseparable from plants in meeting their daily food needs, especially plants as supplementary food. The aim of this study was to investigate of ethnobotany and economic value of spice and condiment plants used by Tamiang tribe in Aceh, Indonesia. A field survey was conducted in three sub-districts, namely Rantau, Seruwai, and Bendahara, Aceh Tamiang District involved 150 respondents (50 individuals from each sub-district) were randomly selected. A total of 31 spices and condiments plants consisting of 26 genera and 18 families was recorded in the study area. Fruits (36%) are the most commonly used parts of plants for spices and condiments, followed by leaves (16%), seeds (13%), rhizome and flower (10% respectively), bulb (6%), and stem and bark (3% respectively). These species were used for preserving traditional cuisines such as bubur pedas, ikan cang rebong, and anyang. Capsicum annuum L has high economic value. The Tamiang tribe has always preserved traditional knowledge of the use of various spices and condiment plants for traditional cuisine.